Novel electrodeposited NiFeP/Zn bifunctional catalytic coating for alkaline water splitting (2023)
ABSTRACT: The shift towards renewable energies has promoted research into electrolysis for the obtention of pure hydrogen since this is a promising energy vector. However, electrolysis is limited due to its low efficiency. In this work, a novel NiFeP/Zn coating electrodeposited on AISI 304 steel is proposed as a bifunctional catalytic electrode for electrochemical water splitting. The leaching of Zn from the coating allows the formation of a diversified surface morphology of the electrode, obtaining an active area 1164 times greater than that of a NiFeP coating. The leaching process also allows the formation of Ni oxides, hydroxides and oxyhydroxides, which are beneficial catalytic compounds for the reactions of interest. XRD characterization indicates the presence of an amorphous structure of the coating due to the presence of P, which provides better catalytic performance for the hydrogen evolution reaction (HER) and oxygen evolution reaction (OER), as well as better corrosion behavior of the electrodes. The electrocatalytic performance of the coating shows overpotentials of 163 mV for HER, and 262 mV for OER in 1 M NaOH at |10| mAcm−2. The full cell test using the NiFeP/Zn coating as bifunctional electrode shows a remarkably low overpotential equal to 1.65 V at 10 mA cm−2 for overall water splitting.